2016
DOI: 10.1021/acs.jpcc.6b01013
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Thermal Effect on the Electronic Properties of Photovoltaic Perovskite CH3NH3PbI3: The Case of Tetragonal Phase

Abstract: Hybrid organic-inorganic perovskites are semiconductors with disordered structures and remarkable properties for photovoltaic applications. Many theoretical investigations have attempted to obtain structural models of the high-temperature phases, but most of them are focused on the mobility of organic components and their implications in material properties. Herein we propose a set of geometric variables to evaluate the conformation of the inorganic framework at each phase of methylammonium lead iodide perovsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 48 publications
4
31
0
Order By: Relevance
“…Moreover, since the organic cation in o-MAPbBr 3 is experimentally observed to be in a fixed orientation in the low temperature phase, a molecular dynamics simulation is deemed unnecessary to provide insight into the nature of the non-covalent interactions involved. Both MAPbI 3 and MAPbBr 3 have previously been explored by molecular dynamics simulations [72][73][74][75], yet insight into the underlying bonding topology is, in our view, and those of others [30], still greatly lacking. We believe that the results presented below on the equilibrium static geometries significantly enhances our current understanding of the bonding scenarios in the…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, since the organic cation in o-MAPbBr 3 is experimentally observed to be in a fixed orientation in the low temperature phase, a molecular dynamics simulation is deemed unnecessary to provide insight into the nature of the non-covalent interactions involved. Both MAPbI 3 and MAPbBr 3 have previously been explored by molecular dynamics simulations [72][73][74][75], yet insight into the underlying bonding topology is, in our view, and those of others [30], still greatly lacking. We believe that the results presented below on the equilibrium static geometries significantly enhances our current understanding of the bonding scenarios in the…”
Section: Resultsmentioning
confidence: 99%
“…[ 48 ] With the assumption that lattice dilation is the dominant factor for the temperature‐dependent shift of the PL maximum, [ 6,12 ] we find tensile strain values of 85–165 MPa (see Section S7 in the Supporting Information for details). However, recent studies demonstrated that the unit cell volume of the orthorhombic phase is smaller than the one of the tetragonal phase, [ 4,45,49,50 ] and thus there should be compressive strain instead of tensile strain to affect the tetragonal inclusions. Room temperature measurements showed that pressure on MAPbI 3 leads to a red shift.…”
Section: Discussionmentioning
confidence: 99%
“…In the pursuit of developing high energy‐conversion efficiency in organic‐inorganic hybrid halide perovskites‐based optoelectronic devices, the reliable information about their electronic structures is indispensable for a deep understanding of the photon harvesting process. It has been reported that the electronic and optical properties of metal halide perovskites can be tuned by several factors, including halide substitution, substrate engineering, annealing treatments, and trap states . Note that all the perovskite films studied in this work (without mentioned fabrication method) are fabricated by spin‐coating solution process, while several reports using thermal evaporation will be marked specifically.…”
Section: Energetics Of Metal Halide Perovskitesmentioning
confidence: 99%